The Influence of Motivation, Competence, and Job Satisfaction with Mediating of Organizational Culture and Moderating of Javanese Culture Based Coaching on Junior High School Principals' Performance in Grobogan Regency - Maftukin, Ali; Wahyudin, Agus; Utomo, Cahyo Budi; Sugi, Sugi (Universitas Negeri Semarang, 2025)
This study aims to analyze the influence of motivation, competence, and job satisfaction on the performance of junior high school principals in Grobogan Regency by considering the role of organizational culture as a mediating variable and Javanese culture based coaching as a moderating variable. This study uses a quantitative approach with path analysis to examine how motivation, competence, and organizational culture affect the performance of junior high school principals in Grobogan Regency. Job satisfaction serves as a mediating variable, while Javanese culture-based coaching acts as a moderator. Data were collected from 100 principals using validated questionnaires, and analyzed with the SEM-PLS method. The results show that motivation, competence, and job satisfaction significantly influence organizational culture, and both motivation and organizational culture significantly enhance principal performance. However, coaching based on Javanese culture and its interaction with organizational culture do not show significant direct effects on performance. Overall, the model demonstrates strong validity, reliability, predictive relevance (Q²), and a high goodness of fit (GoF = 0.562), indicating its robustness in explaining the relationships between the studied variables.